Analysis of Cross-border Distributor Trends in the CEE Agrochemical Markets - Moravec, Lukáš; Tyll, Ladislav; Krause, Josef, 1978-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2014)
The goal of this thesis is to analyze the emerging trends in the cross-border agrochemical distributors' network in Central and Eastern Europe. It aims to answer three research hypotheses and uses desk research methodology to reach this goal. The thesis studies five distributors of agrochemicals considered as pioneers in the industry and assumes their behavior as a proxy for the whole industry behavior. It verifies the first hypothesis that there is an ongoing cross-border consolidation of the distribution network. On the other hand, due to the industry stage and the agrochemicals' market growth it rejects the second hypothesis that there is a pressure on industry profitability. At last, it confirms the third hypothesis that suppliers should consider a change to cope with cross-border customers. In addition, it suggests two areas how to create additional value for the distributors and their suppliers.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses